2015
DOI: 10.1124/jpet.114.222265
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor–Dependent Stanniocalcin 2 Induction by Cinnabarinic Acid Provides Cytoprotection against Endoplasmic Reticulum and Oxidative Stress

Abstract: The aryl hydrocarbon receptor (AhR) is a cytosolic ligandactivated transcription factor historically known for its role in xenobiotic metabolism. Although AhR activity has previously been shown to play a cytoprotective role against intrinsic apoptotic stimuli, the underlying mechanism by which AhR confers cytoprotection against apoptosis is largely unknown. Here, we demonstrate that activation of AhR by the tryptophan catabolite cinnabarinic acid (CA) directly upregulates expression of stanniocalcin 2 (Stc2) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 58 publications
3
61
1
Order By: Relevance
“…Although previous reports have suggested that AhR mediates ROS generation in other tissues such as hepatocytes 48) , we failed to detect the involvement of AhR in indoxyl sulfate-triggered oxidative stress in the vascular endothelium. We obtained similar findings using 3MC, another AhR ligand, in the endothelial model (data not shown).…”
Section: Discussioncontrasting
confidence: 50%
“…Although previous reports have suggested that AhR mediates ROS generation in other tissues such as hepatocytes 48) , we failed to detect the involvement of AhR in indoxyl sulfate-triggered oxidative stress in the vascular endothelium. We obtained similar findings using 3MC, another AhR ligand, in the endothelial model (data not shown).…”
Section: Discussioncontrasting
confidence: 50%
“…To date, although ligand (TCDD)-dependent alterations in AhR structure have been observed using in vitro synthesized [ 35 S]-labeled AhR and proteolysis approaches [64], ligand-specific differences in overall AhR and/or ARNT structure have not yet been reported. However, a recent study was one of the first to clearly demonstrate AhR ligand-specific differential gene induction in a single cell type [65]. Stannocalcin 2 (Stc2) is a gene whose promoter contains numerous DREs [56,65], however, while classical AhR agonists (TCDD, 3MC and BNF) stimulate AhR binding to DREs upstream of CYP1A1 (measured using ChIP analysis) and induced CYP1A1 gene expression in primary hepatocytes, they failed to stimulate Stc2 gene expression or ligand-dependent binding of AhR to Stc2 promoter DREs [56,65].…”
Section: Diversity In Ahr Ligand-dependent Gene Inductionmentioning
confidence: 99%
“…However, a recent study was one of the first to clearly demonstrate AhR ligand-specific differential gene induction in a single cell type [65]. Stannocalcin 2 (Stc2) is a gene whose promoter contains numerous DREs [56,65], however, while classical AhR agonists (TCDD, 3MC and BNF) stimulate AhR binding to DREs upstream of CYP1A1 (measured using ChIP analysis) and induced CYP1A1 gene expression in primary hepatocytes, they failed to stimulate Stc2 gene expression or ligand-dependent binding of AhR to Stc2 promoter DREs [56,65]. In contrast, cinnabarinic acid, a newly identified tryptophan-derived AhR agonist [66], stimulated both AhR binding to the Stc2 promoter DREs and Stc2 gene expression, but failed to stimulate AhR binding to CYP1A1 DREs or induce CYP1A1 gene expression [65].…”
Section: Diversity In Ahr Ligand-dependent Gene Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Recently, CA also has been shown to play a cytoprotective role in endoplasmic reticulum or oxidative stress-induced apoptosis through AHR-dependent induction of stanniocalcin 2 (Stc2) (Joshi et al, 2015). Further investigation of the kynurenine pathway may lead to the identification of additional endogenous AHR ligands.…”
Section: Host Metabolism Of Tryptophanmentioning
confidence: 99%